2021
DOI: 10.7150/jca.52156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognosis-related Hub RNA Binding Proteins Function through Regulating Metabolic Processes in Tongue Cancer

Abstract: RNA binding proteins (RBPs) are dysregulated and associated with the occurrence and development in various malignant tumors. However, the role of RBPs in tongue cancer are largely unclear. Here, by integrating the differential gene expression analysis and the Weighted Gene Co-expression Network Analysis (WGCNA) of TCGA-retrieved RNA-seq data, we identified a total of 171 differential co-expression RBPs. Then, in a protein-protein interaction (PPI) network containing 134 nodes (RBPs) and 315 network edges (RBP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Thus, a high SLC20A1 expression in prostate cancer may be associated with transcriptional regulation. Consistent with the findings of previous studies on breast, pancreatic and tongue cancer (8)(9)(10)(11), SLC20A1 high prostate cancer was associated with poor DSS. In addition, SLC20A1 high prostate cancer was associated with poor DFS and PFS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, a high SLC20A1 expression in prostate cancer may be associated with transcriptional regulation. Consistent with the findings of previous studies on breast, pancreatic and tongue cancer (8)(9)(10)(11), SLC20A1 high prostate cancer was associated with poor DSS. In addition, SLC20A1 high prostate cancer was associated with poor DFS and PFS.…”
Section: Discussionsupporting
confidence: 91%
“…Solute carrier family 20 member 1 (SLC20A1) is a gene that encodes a sodium/phosphate symporter (5,6) and has been proposed to be a viable prognostic marker for breast, tongue and pancreatic cancer (7)(8)(9)(10). Previous data showed that high SLC20A1 expression also indicates poor clinical outcomes for patients with breast cancer subtypes which are treated with endocrine therapy and radiotherapy (11,12).…”
mentioning
confidence: 99%
“…ZC3H12D is also called MCPIP4, C6orf95, and dJ281H8.1. It is a tumor suppressor gene, which plays a critical role in many cancers, including tongue cancer [ 52 ], osteosarcoma [ 13 ] and lung cancer. As for lung cancer, most of previous studies focused on the effect of genetic polymorphisms of ZC3H12D, and little was known about its potential regulatory mechanisms on lung cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 However, the relationship between RBPs and pMMR/MSS CRC has not yet been reported. Therefore, we calculated the DEGs between IC and non-IC in the COAD cohort to intersect with more than 3800 RBPs that have been reported, 21 and 682 differentially expressed RBPs were obtained. Through univariate Cox proportional hazards regression analysis, 22 genes were finally obtained (figure 2A).…”
Section: Gbp2 Expression Is Upregulated In Icmentioning
confidence: 99%